DETERMINANTS OF AUDIT REPORT LAG: EVIDENCE FROM QUOTED MANUFACTURING FIRMS ON THE NIGERIAN STOCK EXCHANGE (Journal of Global Accounting, 2023)
This study investigates the determinants of audit report lag of quoted manufacturing firms in Nigeria. The study specifically examines the effect of audit tenure, client size, board size, audit firm size, CEO Duality and board independence on audit report timeliness of quoted manufacturing firms. The study is anchored on agency theory. The study adopts the ex-post facto research design. The sample comprised of sixty six (66) manufacturing firms quoted on the Nigerian Stock Exchange (NSE) as at 31st December• The study used secondary data obtained from annual reports and accounts. The data were analysed using multiple regression technique. The results showed that audit tenure and board size were negative but not statistically significant. The surrogate for client size was positive but not significant; while, audit firm size, board independence, and CEO-duality were all positive and significant. Consequent on these findings, it was recommended amongst others that, companies maintain audit firms for a reasonable amount of time before rotation. Studies have shown that large and internationally affiliated audit firms conduct their audit assignments relatively faster than smaller firms. It is recommended that companies employ the services of audit firms relative to the size of the firm.
Keywords: Audit Report Lag; Audit Tenure; Client Size; Board Size; Audit Firm Size; CEO duality; Board Independence; Agency Theory